Two new species of Suberitida (Porifera, Heteroscleromorpha) from the Bering Sea - Lehnert, Helmut (Zootaxa, 2017)
Two new species, Plicatellopsis borealis and Spongosorites beringensis, from the Bering Sea are described; both belong to genera previously not reported from the area. The genus Plicatellopsis, Burton, 1932 (Porifera, Suberitida, Suberitidae) contains five valid species, all recorded from the southern hemisphere. The record of P. borealis n. sp. from the Bering Sea is consequently the first record of the genus from the northern hemisphere. The genus Spongosorites Topsent, 1896 (Porifera, Suberitida, Halichondriidae) contains 22 valid species but none reported from the North Pacific Ocean, Bering Sea or the Arctic Ocean. The geographically closest records are six species occurring in the North Atlantic Ocean. So the description of Spongosorites beringensis n.sp. is the first record of the genus in the region.